Co-application of molybdenum and selenium fertilizers increase uptake, recovery and harvest index of molybdenum and selenium in pepper crop. (28th January 2016) - Zhang, Mu; Hu, Chengxiao; Zhao, Xiaohu; Tan, Qiling; Sun, Xuecheng
ABSTRACT: A pot trial was conducted to clarify the interactions of molybdenum (Mo) and selenium (Se) fertilizers on uptake, harvest index and recovery of Mo and Se by pepper crop ( Capsicum frutescens L.). Mo was applied at three rates (0, 0.15 and 0.3 mg kg −1 ) and Se at three rates (0, 0.4 and 0.8 mg kg −1 ) in soil. Appropriate application of Mo increased Se concentrations in pepper fruit, stem, leaf and root especially in the presence of Se fertilizer. Appropriate application of Se increased Mo concentrations in pepper fruit, stem, leaf and root particularly in the presence of Mo fertilizer. Both Mo and Se had beneficial effects on harvest index and recovery of Mo and Se. These results indicated that there is significant synergetic effect on Mo and Se absorption and translocation, and co-application of these two elements is necessary to produce Mo and Se-rich pepper.